En amont d’une indépendance. Les relations entre Lisbonne et Rio de Janeiro, 1807-1822 - Cristina Climaco (Les Cahiers ALHIM)
It is to analyze the mutations caused by the French invasions in relations between France and the colony, including the dislocation of the center of the empire to America and the attempt to restructure it. The creation of the United Kingdom of Portugal and Brazil is indicative of the new status of the former colony in the new empire. The resistance to this new order follows the confrontation between two competing visions, including the large differences could lead to the independence of Brazil.